Staging and In-Plane Superstructures Formed in Layered NaMO2 {M = Sc, Ti, V, Cr, Mn} during Na De-Intercalation: A Computational Study. Issue 4 (16th January 2015) - Aryanpour, M.; Miara, L.; Ryu, Y.-G.
Abstract : Layered alkaline-metal oxides constitute one of the most important classes of modern materials for battery electrodes and energy applications. They serve also as a standard template for designing more complicated compounds through metal mixing or anion substitution. The sodium version of these oxides has become the topic of intensive research because of the successful applications of their lithium analogue structures. Electrochemical characterization of sodium ternary oxides often shows voltage plateaus, some possibly caused by preferred atomic orderings of cation, that tend to limit the full charging and the capacity retrieval. Understanding the behavior of these materials at an atomistic level is crucial to their maximal exploitation. To this end, we report on a set of systematic GGA+U DFT computations of model system O3-NaMO2 (M = Sc, Ti, V, Cr, Mn). We find that Na-vacancies prefer staging n = 1 (each layer) over n = 2 (every other layer) in all those structures, that is they tend to first spread across sodium layers than into the layers. Similarities and differences in the details of the staging behavior among the 5 metal oxides are discussed and shown to be explainable by considering local charge densities. As an application of these computations, trends of ionic diffusion in those materials are predicted and compared with experimental results.